Option Auctions - Hendershott, Terrence; Khan, Saad Ali; Riordan, Ryan (Review of Financial Studies, 2026)
Abstract Wholesale market makers pay for retail options orders that must be executed on exchanges. Payment for order flow (PFOF) wholesalers compete via price improvement in exchange auctions. To attract retail orders, wholesalers run more auctions when their recent price improvement has been lower. However, auction price improvement lowers market maker revenues. Wholesalers earn revenues to pay PFOF in nonauction trades where their designated market maker status increases their execution priority. While some auctions produce substantial price improvement, most do not have multiple bidders offering meaningful price improvement. Overall, options market structure better promotes competition in auctions than in nonauctions.